2008
DOI: 10.1002/chin.200829013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Al—B—Nb—Ti System. Part 2. Thermodynamic Description of the Constituent Ternary System B—Nb—Ti.

Abstract: Equilibria E 4000The Al-B-Nb-Ti System. Part 2. Thermodynamic Description of the Constituent Ternary System B-Nb-Ti. -(WITUSIEWICZ*, V. T.; BONDAR, A. A.; HECHT, U.; REX, S.; VELIKANOVA, T. Y.; J. Alloys Compd. 456 (2008) 1-2, 143-150; RWTH Aachen, ACCESS e.V., D-52072 Aachen, Germany; Eng.) -Schramke 29-013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 1 publication
2
28
0
1
Order By: Relevance
“…[39] This is due to the thermodynamic instability of AlB 2 due to the aforementioned decomposition reaction (Eq 1), though it should be noted that the transformation rate is slow. [26,40] The computationally determined Al-Ti-B isotherms generated by Witusiewicz et al [41] have been confirmed by experimental results and provide reliable equilibrium phase relations at 1000°C (Fig. 1c).…”
Section: 22mentioning
confidence: 55%
See 1 more Smart Citation
“…[39] This is due to the thermodynamic instability of AlB 2 due to the aforementioned decomposition reaction (Eq 1), though it should be noted that the transformation rate is slow. [26,40] The computationally determined Al-Ti-B isotherms generated by Witusiewicz et al [41] have been confirmed by experimental results and provide reliable equilibrium phase relations at 1000°C (Fig. 1c).…”
Section: 22mentioning
confidence: 55%
“…Fig. 1 Isothermal ternary diagrams at 1000°C of, (a) Al-B-C system as presented by Grytsiv; [36] (b) Al-Ti-C system as presented by Pietzka and Schuster, where H and P represent the Ti 2 AlC and Ti 3 AlC phases, respectively, [30] and; (c) Al-Ti-B system as presented by Witusiewicz et al [41] b 2.2 Processing 2.2.1 Preparation of Carbide Preforms. The Ti 2 AlC/ B 4 C powders were mixed in the molar ratios of 4.5:5 and 7:4 for the BR and TiR composites, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The lattice parameters of TiB hardly differ in the binary and ternary alloys, which agrees well with EMPA data, according to which the solubility of aluminum in this boride is no more than 0.05 at.%. As shown by DTA, the greater aluminum content, the higher the melting temperature of the alloys and the temperature of β + TiB ↔ α phase transition [31].…”
Section: As-cast Ternary Alloysmentioning
confidence: 98%
“…For this reason, a scientifically sound selection of a doping agent is hardly possible. The previous papers focused on examining the phase equilibria and constructing the phase diagrams in titanium corners of the following ternary systems: Ti-Al-B [32], Ti-Si-B [12,33], Ti-Ge-B [34,35], and Ti-Sn-B [36] ( Table 2). The objective of this paper is to analyze how doping with p-elements (Al, Si, Ge, Sn) and zirconium influences the structure and mechanical properties (hardness from room temperature to 900°C, strength, and plasticity) of alloys based on the two-phase titanium-boride eutectic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation